1988
DOI: 10.1128/aem.54.7.1831-1837.1988
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein Isothiocyanate-Labeled Lectin Analysis of the Surface of the Nitrogen-Fixing Bacterium Azospirillum brasilense by Flow Cytometry

Abstract: The cell surface of Azospirillum brasilense was probed by using fluorescein isothiocyanate (FITC)-labeled lectins, with binding determined by fluorescence-activated flow cytometry. Cells from nitrogen-fixing or ammonium-assimilating cultures reacted similarly to FITC-labeled lectins, with lectin binding in the following order: Griffonia simplicifolia II agglutinin > Griffonia simplicifolia I agglutinin > Triticum vulgaris agglutinin > Glycine max agglutinin > Canavalia ensiformis agglutinin > Limaxflavus agglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Also, various lectins may agglutinate with different strengths to the same sugar class. Many bacterial species have different sugar residues on the cell surface such as nitrogen-fixing bacterium Azospirillum brasilense, which was described to bind nearly all of the above-described lectins (Yagoda-Shagam et al, 1988). Additionally, the presence of sugar residues on the bacteria's surface may depend on the growth conditions, influencing therefore the agglutination strength and the intensity of the label in the end (Heine et al, 2009).…”
Section: Lectin Labellingmentioning
confidence: 99%
“…Also, various lectins may agglutinate with different strengths to the same sugar class. Many bacterial species have different sugar residues on the cell surface such as nitrogen-fixing bacterium Azospirillum brasilense, which was described to bind nearly all of the above-described lectins (Yagoda-Shagam et al, 1988). Additionally, the presence of sugar residues on the bacteria's surface may depend on the growth conditions, influencing therefore the agglutination strength and the intensity of the label in the end (Heine et al, 2009).…”
Section: Lectin Labellingmentioning
confidence: 99%
“…In previous works by Yagoda-Shagam et al [5] and Del Gallo et al [6] fluorescein isothiocyanate-labelled WGA was shown to bind to A. brasilense cells and this process was inhibited by N-acetyl-D-glucosamine. The increase in nitrogenase and GS activities and ammonia excretion observed by us probably results from the WGA binding to bacterial cell surface.…”
Section: Discussionmentioning
confidence: 86%
“…It remains unclear which structures of the cell surface of A. brasilense are responsible for the binding of WGA. Besides lipopolysaccharides and capsule polysaccharides, whose N-acetyl-Dglucosamine residue are presumed [5,16,17] to interact with WGA, the lectin of A. brasilense [18] may be involved in the reception of WGA. It is a cell surface glycoprotein which incorporates N-acetyl-D-glucosamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescent lectins (table II), which bind to the carbohydrate moiety of glycoproteins and glycolipids on the cell membrane outer surface, are now popularly used in conjunction with, or in place of monoclonal antibodies, for the same applications as the latter. Lectins and FCM have been used to characterize the sugars present on the outer surface of the nitrogen-fixing bacterium, Azospirillum brasilense, which is possibly involved in the colonization of host tissue during plant-bacteria symbiotic association [210].…”
Section: Detection Of Antigenic Determinants Glycosylated Cellular Cmentioning
confidence: 99%